Contributions of self-criticism and shame to hoarding. (April 2018) - Chou, Chia-Ying; Tsoh, Janice; Vigil, Ofilio; Bain, David; Uhm, Soo Y.; Howell, Gillian; Chan, Joanne; Eckfield, Monika; Plumadore, Julian; Chan, Elena; Komaiko, Kiya; Smith, Lauren; et al.
Abstract: Pathological hoarding-related beliefs, such as need to control possessions, and inflated sense of responsibility over possessions, have been used to explain the development of symptoms of hoarding disorder (HD). While these beliefs have been the focus of the current standard treatment for HD, it is of significant clinical interest to further examine other constructs that may be linked to, or may underliethese beliefs, as well as the pathology of HD. To this end, the current study aimed to build on existing findings regarding the relationship of compromised self-identity with HD. Specifically, we investigated the relationship between self-criticism, shame, hoarding beliefs, and severity of HD symptoms among 104 treatment-seeking individuals with HD. We found that self-criticism and shame are positively associated with HD symptoms and hoarding related beliefs. Moreover, our data shed light on how these factors are connected by elucidating the indirect effects of self-criticism and shame on HD symptoms, mediated through beliefs about inflated sense of responsibility over possessions. The findings have implications for future research to examine interventions targeting compromised self-identity, including self-criticism and shame, among individuals with HD. Highlights: Higher self-criticism and shame predict greater hoarding symptoms. Higher self-criticism and shame predict greater hoarding related beliefs. Hoarding beliefs mediate relationships between self-criticism, shame, and hoarding symptom.